TURKEY’S NEW FOREIGN POLICY: THE QUEST FOR REGIONAL HEGEMONY IN THE MIDDLE EAST? - Arin, Kubilay Yado (The Copernicus Journal of Political Studies, 2018)
The last decades saw Turkey evolving from its Cold War era model of foreign relations, when it was the bastion of the West in the region, which involved alliance with the US and Israel. Following the doctrine of Ahmed Davutoĝlu, a theoretician of the Islamic Justice and Development Party (AKP), which rose to power in 2002, Turkey opened to the neighbouring states, striving to become a regional power by diplomatic rather than military means and through cultural and economic incentives. Both the internal and international actions of AKP governments were initially successful, and Turkey with its version of Islamic democracy was considered a model during the Arab Spring and a sound counterbalance to such countries as Iran. However, Turkey’s bid to join the EU was stalled, and its approach to the civil war in Syria as well as other issues has been heavily criticized both in the West and in the region. The internal tensions are growing too, as the government has failed to recognize the rights of large minority groups, particularly the Kurds and the Alevi, which may threaten the integrity of the country.